Role of the Agriculture and Tourism Sector in the Economy of Nepal - Saud, Ramesh Kumar (The Management Review, 2025)
The primary pillar of the Nepalese economy is agriculture. In addition, Nepal’s tourism industry is a significant and highly promising economic sector. This study examines how Nepal’s GDP is impacted by the tourism industry, which generates foreign exchange earnings, and the agriculture sector, which encompasses forestry, fisheries, and agriculture. Using secondary time series data from 1995 AD to 2020 AD, this study investigates the economic contributions of the tourism and agriculture industries to the GDP of Nepal. For trend analysis, this study additionally employed secondary time series data on the value of the agricultural sector’s contribution to GDP from 1965 AD to 2023 AD. Ordinary least squares regression has been used to evaluate secondary time series data from the World Bank-World Development Indicators. This paper used agriculture, forestry, and fishing as primary independent variables, with foreign tourism receipts serving as a supporting independent variable. The GDP was the dependent variable. This study came to the conclusion that the agriculture sector and GDP have a favourable and significant relationship. Additionally, this paper’s empirical findings demonstrated a positive and insignificant relationship between GDP with foreign tourism receipts.